2018
DOI: 10.22159/ajpcr.2018.v11i1.21537
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Systematization of a Comprehensive Medication Management (Cmm) Service Delivered to Women With Breast Cancer

Abstract: Objective: The aim of the present study was to describe the process of implementation and systematization of a comprehensive medication management (CMM) service, from the perspective of the participants involved, in a high complexity service that cares for women with breast cancer in Brazil.Methods: A qualitative study that utilized action research that followed the procedures proposed by Kurt Lewin and the ethical and clinical principles of pharmaceutical care practice. Data collection techniques were partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…As stressed by Rosenthal et al (46), staying in one's own familiar environment and avoiding leaving one's comfort zone is ingrained in pharmacist's culture. In addition, as revealed in other studies (16,(47)(48)(49), action research encouraged individual and group reflections on new circumstances and allowed for the conception of the most fitting organizational model for an efficient implementation of CMM services.…”
Section: Quantitative Resultsmentioning
confidence: 89%
“…As stressed by Rosenthal et al (46), staying in one's own familiar environment and avoiding leaving one's comfort zone is ingrained in pharmacist's culture. In addition, as revealed in other studies (16,(47)(48)(49), action research encouraged individual and group reflections on new circumstances and allowed for the conception of the most fitting organizational model for an efficient implementation of CMM services.…”
Section: Quantitative Resultsmentioning
confidence: 89%
“…This relationship was also identified by Ribeiro et al (2018), who concluded that educational support and the development of service management skills by pharmacists are essential to achieve results and overcome barriers [66]. On this aspect, it is important to point out that, although the educational environment is fundamental for the implementation process, initiatives of universities or other institutes should consider the local autonomy and that of professionals for the continuity of the pharmaceutical care service.…”
Section: Discussionmentioning
confidence: 97%
“…This is a prospective study that was developed in the Oncology sector of a highly complex university hospital in the state of Minas Gerais, Brazil. This hospital is a reference for more than 3 million people in 86 municipalities of the Northern Triangle of Minas Gerais 21 and is an important reference in the treatment of women with breast cancer in the region.…”
Section: Methodsmentioning
confidence: 99%
“…This service is offered by pharmacists according to the theoretical framework of Pharmaceutical Care Practice, which was developed by Cipolle, Strand and Morley 22 and Ramalho de Oliveira. 23 This service was previously proposed by Ribeiro 21 to constitute a field of clinical practice and a structure for the production of knowledge in the care of women undergoing breast cancer treatment. 24,25 A total of 81 patients were included in the study, with a minimum age of 18 years old and who received treatment with taxanes (paclitaxel or docetaxel) according to one of the protocols: ACT (doxorubicin, cyclophosphamide and paclitaxel) or ACT-H (doxorubicin, cyclophosphamide, paclitaxel and trastuzumab), both with 80 mg/m 2 of paclitaxel per week during 12 weeks.…”
Section: Participantsmentioning
confidence: 99%